Scheduling Ocean Color Observations for a GEO-Stationary Satellite - Frank, Jeremy; Do, Minh; Tran, Tony (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
The GEO-Stationary Coastal and Air Pollution Events (GEO-CAPE) mission plans to put a visible spectrum imaging instrument on a satellite in geo-stationary orbit to perform ocean color remote sensing. Two different instrument designs, Filter Radiometer (FR) and COastal Ecosystems Dynamic Imager (COEDI), with different shape for the imaged area and image acquisition time, are being evaluated. Scheduling observations for either instrument requires optimizing science objectives in the presence of predicted cloud cover and available daylight. We model this scheduling problem as both Mixed Integer Linear Program (MILP) and Constraint Programming (CP) problems, and compare these two formulations for FR and COEDI using real cloudiness data collected at different times throughout the year. Our results show that MILP is the more suitable technique, and the schedule quality metric shows FR is the preferred design. We have reported our results to the GEO-CAPE mission team to assist them making an informed decision for the next step in formulating this mission.